A Simple Probabilistic Proof for the Alternating Convolution of the Central Binomial Coefficients. Issue 3 (3rd July 2018) - Pathak, Ashok Kumar
ABSTRACT: This note presents a simple probabilistic proof of the identity for the alternating convolution of the central binomial coefficients. The proof of the identity involves the computation of moments of order n for the product of standard normal random variables.